T. S. Eliot & organicism - Diaper, Jeremy (Clemson University Press, 2018)
"T. S. Eliot and Organicism covers new ground by demonstrating that a thorough understanding of Eliot's engagement with agriculture and the environment is vital to our interpretation of his work. This book makes an important contribution to environmental modernism and establishes that Eliot had a pivotal role in the emergence of the organic movement"--